The Analysis of Regional Taxes Effectiveness and Contribution to Regional Original Income of South Sumatra Province: A Post-Covid 19 Study - Savira, Okky (Pt. Anagata Sembagi Education, 2025)
The Covid 19 pandemic has caused various changes in various aspects of life, including in terms of a country's economy. This study examines the effectiveness and contribution of regional taxes to the original regional income of the province of South Sumatra in the period 2021-2023. The results of the analysis using the quantitative descriptive method show that there are fluctuations in the contribution and effectiveness of regional taxes after Covid 19 in South Sumatra. This is understandable considering that a province is in a state of recovery since social restrictions on the community which led to changes in the rate of economic activity that occurred. However, the contribution of regional taxes in South Sumatra is still the largest source of original regional income and is still at a very effective level.